Effects of change in residence to a mountain village on children's melatonin responses. Issue 1 (2nd January 2021) - Noi, Shingo; Shikano, Akiko; Yamada, Naoko; Tanaka, Ryo; Tanabe, Kosuke; Tsuji, Hideyuki
ABSTRACT: Sleep problems are especially serious in Japan. The purpose of the present study was to clarify the effects of a shift of residence to a mountain village on children's melatonin responses. The participants were 19 children (nine males and ten females, 10–15 years old) who participated in the Mountain Village Educational Program. After excluding a girl with confirmed deficits, the data of 18 participants were used for analysis. We measured salivary melatonin concentration and assessed the self-completed questionnaire survey on sleep situation. Although the proportion of people who showed a greater salivary melatonin concentration at night than in the morning immediately after starting the Mountain Village Educational Program was 50%, after that it was shown that melatonin concentration increased at night and decreased in the morning. The results demonstrated that all participants showed a salivary melatonin secretion pattern of night > morning after approximately 3.5 months. Based on these findings, the Mountain Village Educational Program, which involves a shift of residence to a mountain village, has the potential to improve children's sleep. Abbreviations : DLMO: Dim light melatonin onset; MVEP: Mountain Village Educational Program